TÜRKIYE AND THE TRANSFORMATION FROM OTTOMAN TO A MODERN REPUBLIC: A SOCIAL HISTORICAL PERSPECTIVE - Ma'adul Yaqien Makkarateng; Andi Darna; Fauzan Samad; Fahmi Yusuf (Program Studi Sosiologi Universitas Malikussaleh, 2026)
This study aims to discuss Turkey, an empire that emerged after the end of the Umayyad, Abbasid, Fatimid, Seljuk, Ayyubid, and Mamluk periods. This study uses a qualitative method with a social history approach. The social history theory is a way to systematize, categorize and provide a social historical interpretation of the development of the Ottoman Empire until it became Modern Turkey. This study concluded that the Ottomans became one of the great Islamic empires with a huge territory that defeated the previous dynasties. The territory of power stretches from the continent of Asia, Africa and even to Europe. In 1942 the Ottoman caliphate changed from an empire to the Republic of Turkiye spearheaded by Mustafa Kemal Attaturk. In this phase Turkey was subjected to a wave of secularism and westernization that turned into a massive revolution and the jargon that emerged was the absolute separation of religious and state affairs in the truest sense. The next phase was the re-emergence of Islamic power which was started by Necmettin Erbakan by founding the Refah party. Despite being overshadowed by a powerful military force, the Islamist group has gained public sympathy. Today, modern Islamist groups continue to have public support led by Recep Tayyip Erdoğan with the AKP party. Various political, social, economic and influential achievements continued to be achieved during this leadership. Domestic political stability with the Kurds has improved in addition to socio-political stability in the Middle East, Asia and Europe. In the context of social history, Turkey underwent a transformation starting from a monarchical caliphate, then to a secular republic and finally entering the phase of the modern Islamic republic.